Gambaran Pengetahuan Pasien Terhadap Hak dan Kewajiban Pasien SC (Sectio Caesaria) Rawat Inap Di RSUD Dr. Moewardi Surakarta Mei Tahun 2014 - Bekti Suharto - Poltekkes Bhakti Mulia Sukoharjo (Indonesian Journal on Medical Science, 2016)
ABSTRACT: The results of a preliminary study based on reports 10 disease hospitalization in 2013 the number of cases as many as 1,502 patients sectio Caesaria. With the number of such patients in the explanation / release of such information is critical to patients so that they are ready to accept whatever will happen and it will not pursue a lawsuit after the action approved by the patient's informed consent / approval of medical action. Knowing picture of patients' knowledge of the rights and obligations of SC patients (Sectio Caesarea) Inpatient Hospital Regional General Dr. Moewardi Surakarta in May 2014. observation and interview, descriptive study, cross-sectional approach. The object of research patients sectio Caesaria in May 2014, and the total sample population of patients in May. Of the total 19 patients who received general information about the apparent approval of 16 (84.2%) and unclear (15.8%), clearly understand the information 17 (89.5%) and unclear 2 (10.5% ), clear information about the patients' rights 19 (100%), information on the obligations of patients / families obviously 19 (100%), medical information clearly consent 14 (73.7%) and unclear 5 (26.3%), information clearly written approval of medical action 19 (100%) or all of the total patients, explanatory information as clear approval of medical measures 19 (100%) or all of the total patients, clear information on the risk as much as 17 (89.5%) and unclear 2 (10 , 5%), information and signed an agreement with consciousness itself is obviously 19 (100%). Policies release procedures and information General Consent has been better then need to be improved, clarified in the delivery of information.Keywords: Patient, Medical Officer, and General Consent in patients SC (Sectio Caesarea) Abstraksi : Hasil studi pendahuluan berdasar pada laporan 10 besar penyakit rawat inap tahun 2013 jumlah kasus sectio caesaria sebanyak 1.502 pasien. Dengan jumlah pasien tersebut maka dalam penjelasan/ pemberian informasi tersebut sangat penting kepada pasien agar mereka siap menerima apapun yang akan terjadi dan tidak akan melakukan gugatan setelah dilakukan tindakan yang sudah disetujui pasien dengan informed consent/ persetujuan tindakan medis. Mengetahui gambaran pengetahuan pasien terhadap hak dan kewajiban pasien SC (Sectio Caesaria) Rawat Inap di Rumah Sakit Umum Daerah Dr. Moewardi Surakarta bulan Mei tahun 2014. Observasi dan wawancara, jenis penelitian deskriptif, pendekatan cross sectional. Objek penelitian pasien sectio caesaria pada bulan Mei tahun 2014, populasi dan sampel total pasien pada bulan Mei. Dari total 19 pasien yang mendapatkan informasi tentang persetujuan umum jelas 16 (84,2%) dan belum jelas (15,8%), memahami informasi jelas 17 (89,5%) dan belum jelas 2 (10,5%), informasi tentang hak pasien jelas 19 (100%), informasi tentang kewajiban pasien/ keluarga jelas 19 (100%), informasi persetujuan tindakan medis jelas 14 (73,7%) dan belum jelas 5 (26,3%), informasi persetujuan tertulis tindakan medis jelas 19 (100%) atau semua total pasien, informasi penjelasan persetujuan tindakan medis sebanyak jelas 19 (100%) atau semua total pasien, informasi mengenai risiko sebanyak jelas 17 (89,5%) dan belum jelas 2 (10,5%), informasi dan menandatangani persetujuan dengan kesadaran sendiri jelas 19 (100%). Kebijakan pelepasan prosedur dan informasi General Consent sudah baik maka perlu ditingkatkan, diperjelas dalam penyampaian informasi.      Kata kunci : Pasien, Petugas Medis,dan General Consent pada pasien SC(Sectio Caesarea)